IDENTIFIKASI PENYESUAIN GAYA HIDUP DIKARENAKAN KEBISINGAN PESAWAT DI BANDARA INTERNASIONAL AHMAD YANI DAN SEKITARNYA - Abdusalam Masaud; Kismartini Kismartini; Haryono S Huboyo (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Noise is one of the most common items used by aircraft around the world , there are About 50,000  commercial  flights  each  day  around  the word and 3 million people traveling . In the operational of aviation in Ahmad Yani International Airport Semarang  , an airplane can make some noise. The noise is a sound that  unwanted  in a place and time scale, it can make some disturbance that influence human freshness and health. Particularly for Residents whom living  very close by the airport such as Graha Padma and Tambakharjo. It is commonly believed that people adapt rather easily to noise. This  research reviews the available data , finding little evidence that any adaptation occurs in community close by airport .however, is open to alternative interpretations. The present study, examining reactions   noise effect  from the airport daily operations on residents near by the airport and how they can adapting with the aircraft noise in them daily lifestyle .first of all , we  measured  the noise inside Graha Padma and Tambakharjo in 23 points using apparatus  sound level meter, Taking into consideration different locations ,times and days . we classification this area  into three , most affected area , affected area and low affected area according to the levels of noise .we took  30  random simples of people taking into consideration different times ,days , age, gender and distance. This study wants to suggest that the airport should  take a new  bigger role to minimize the noise and people whom living around the airport should follow some steps to adapting or avoid the aircraft noise. Keywords : Noise , community ,adaptation and Ahmad Yani Airport Semarang